“ME URGEE SE ME SUMINISTRE DE SUS BIENES LOS ALIMENTOS”: FEMALE STRATEGIES IN DOMESTIC DISPUTE RESOLUTION. 1800-1850, CENTRAL VALLEY OF CHILE - Bravo Olmedo, Valentina (Revista de Historia Social y de las Mentalidades, 2016)
This article aims to analyze the practices of  solving women domestic conflicts in front  of the justice in the Partidos of Quillota,  Aconcagua and Santiago between 1800 and  1850, through a review of civilian trials for  food, by alimony brought by married women  and single. The analyzed period represents a  process of legitimizing an institutional legal  system. However, conflict resolution practices  were accompanied by other border practices,  where law and custom were in constant  dialogue. In this context, we propose that  women used to resort to institutional justice  male claiming protection for themselves and  their children, as part of a host of strategies  that were part of negotiated justice, which  meant, by these, a development of resistance  strategies involving gender, legal culture  and advertising the conflict. Consequently,  we distinguish married women, protected by  the institution of marriage, who developed  strategies linked to hegemonic ideals, in order  to obtain a pension corresponding to their  needs. In other hand, single women had to  resort to wider strategies, that committed the  solidarity of its close, disclosure of conflict  and women's honor
Keywords: Married women; Single women; Negotiated justice; Alimony